MASJID JAMI’ KEBON JERUK: MENJADI MARKAZ DAN PENJAMIN JAMA’AH TABLIGH DARI SELURUH DUNIA - Muhammad Adlin Sila (Harmoni, 2016)
This paper examines the role of foreign proselytizers in the development of religious life in Indonesia by investigating foreign attendances in Masjid Kebon Jeruk, Taman Sari, West Jakarta. The mosque has been long popular for its fiunction as a headquarter for the followers of a transnational Islamic movement, Jama’ah Tabligh, from all over Indonesia since long time ago. But little study has undergone to explore the role of this mosque as a host institute for foreign proselytizers from different countries especially from India, Pakistan and Bangladesh or abbreviarted as IPB. In addition, the mosque also hosts those who come from other countires such as Africa, Europe, America and Australia. I met a few of them who just dropped by for a couple of days and joint the group from Indonesia to do dakwah or khuruj on foot to all parts of Indonesia. The research findings show that the role of Masjid Kebon Jeruk is twofold: the first is to function as headquarter for members of Jama’ah Tabligh in Indonesia, and second, to function as host institute for foreign followers of Jama’ah Tabligh from all over the world.